2020
DOI: 10.3390/nu12123855
|View full text |Cite
|
Sign up to set email alerts
|

Milk Containing A2 β-Casein ONLY, as a Single Meal, Causes Fewer Symptoms of Lactose Intolerance than Milk Containing A1 and A2 β-Caseins in Subjects with Lactose Maldigestion and Intolerance: A Randomized, Double-Blind, Crossover Trial

Abstract: Acute-feeding and multiple-day studies have demonstrated that milk containing A2 β-casein only causes fewer symptoms of lactose intolerance (LI) than milk containing both A1 and A2 β-caseins. We conducted a single-meal study to evaluate the gastrointestinal (GI) tolerance of milk containing different concentrations of A1 and A2 β-casein proteins. This was a randomized, double-blind, crossover trial in 25 LI subjects with maldigestion and an additional eight lactose maldigesters who did not meet the QLCSS crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…The authors concluded, inter alia, that given the relative benefits of the A2A2 milk for both lactosetolerant and -intolerant subjects, some perceived symptoms of lactose intolerance may stem from inflammation relating to A1 beta-casein and its derivative bBCM7. Two further Chinese crossover studies, one of 600 adults [87] and another of 80 school children [81], have confirmed the previous digestive discomfort findings relating to A1 versus A2 beta-casein and also provided confirmatory evidence supporting interactions between A1 beta-casein and lactose intolerance that did not apply with the A2 beta-casein diet. A subsequent American study published in 2020 has confirmed the findings that discomfort symptoms among persons who consider themselves lactose intolerant are increased when the milk contains A1 beta-casein [87].…”
Section: Gut Conditionssupporting
confidence: 66%
See 1 more Smart Citation
“…The authors concluded, inter alia, that given the relative benefits of the A2A2 milk for both lactosetolerant and -intolerant subjects, some perceived symptoms of lactose intolerance may stem from inflammation relating to A1 beta-casein and its derivative bBCM7. Two further Chinese crossover studies, one of 600 adults [87] and another of 80 school children [81], have confirmed the previous digestive discomfort findings relating to A1 versus A2 beta-casein and also provided confirmatory evidence supporting interactions between A1 beta-casein and lactose intolerance that did not apply with the A2 beta-casein diet. A subsequent American study published in 2020 has confirmed the findings that discomfort symptoms among persons who consider themselves lactose intolerant are increased when the milk contains A1 beta-casein [87].…”
Section: Gut Conditionssupporting
confidence: 66%
“…Two further Chinese crossover studies, one of 600 adults [87] and another of 80 school children [81], have confirmed the previous digestive discomfort findings relating to A1 versus A2 beta-casein and also provided confirmatory evidence supporting interactions between A1 beta-casein and lactose intolerance that did not apply with the A2 beta-casein diet. A subsequent American study published in 2020 has confirmed the findings that discomfort symptoms among persons who consider themselves lactose intolerant are increased when the milk contains A1 beta-casein [87]. Additionally, in a subset of subjects who were identified as lactose maldigesters using a hydrogen breath test, the level of breath-hydrogen was higher when the diet contained A1 beta-casein, despite the milks containing no difference in lactose content.…”
Section: Gut Conditionssupporting
confidence: 66%
“…This process is known to generate extra sweetness and may also have an impact on the nutritional value of the hydrolyzed milk [52]. More recently, the use of "A2 milk" has been shown to reduce some of the gastrointestinal discomfort associated with drinking ordinary cow's milk in individuals with LI [61]. "A2 milk" is a variety of cow's milk containing mostly A2 beta-casein (like human milk, sheep and goat's milk) that does not metabolize to the peptide beta-casomorphin-7 (BMC-7), which is implicated in adverse gastrointestinal effects, including inflammation [62].…”
Section: Management Of Lactose Intolerancementioning
confidence: 99%
“…"A2 milk" is a variety of cow's milk containing mostly A2 beta-casein (like human milk, sheep and goat's milk) that does not metabolize to the peptide beta-casomorphin-7 (BMC-7), which is implicated in adverse gastrointestinal effects, including inflammation [62]. Interestingly, the gastrointestinal symptoms resulting from the ingestion of cow's milk in LI individuals are decreased when milk enriched in A2 beta-casein is consumed in place of regular milk (which contains A1 beta-casein) [61]. This indicates that the gastrointestinal symptoms due to LI might be confounded by the beta-casein variant present in milk.…”
Section: Management Of Lactose Intolerancementioning
confidence: 99%
“…It did not aggravate such gastrointestinal dysfunctions in subjects with lactose intolerance (He et al, 2017 ). Recent clinical studies have demonstrated that gastrointestinal symptoms of milk intolerance can be avoided by consuming milk containing only the A2 β-casein (Sheng et al 2019 ; Ramakrishnan et al 2020 ; Kay et al 2021 ). Likewise, cow milk protein allergy can be associated with IgE reactions, and immediate reaction symptoms include anaphylaxis, edema, and much gastrointestinal distress such as vomiting, diarrhea, and bloody stools (Fiocchi et al 2010 ).…”
Section: Cow Products For Human Health Managementmentioning
confidence: 99%